(untitled) (Tanzania Medical Journal, 2025)
Background The effective use of well-designed electronic Pharmacy Information Systems (ePIS) is critical in supporting clinical decision-making and detecting medication errors in hospital settings. These systems play a vital role in preventing medication errors, a significant factor contributing to patient safety. Globally, 6% of hospitalizations result from such errors. In this study, we aimed to assess the design, usage level and predictors of ePIS adoption in hospitals in Dar es Salaam, Tanzania. Methodology A cross-sectional survey was conducted from November 2019 to January 2020 across 44 (86%) eligible hospitals in Dar es Salaam to assess the proportion meeting recommended ePIS standards. Functionalities were categorized into four classes: patient data, prescription, clinical decision support (including alerts for drug interactions, allergies, dosages, indications, and side effects), and dispensing and administration. Additionally, the usage level of these functionalities among healthcare providers was evaluated using a self-reported questionnaire. Adjusted odds ratios (AOR) with 95% confidence intervals (CI) identified independent predictors of ePIS usage levels. Results About one-third of the assessed hospitals had ePIS with recommended functionalities. The most common were patient data (74%), followed by medication dispensing and administration (42.2%), and prescription (24.1%), with none supporting clinical decision-making. Utilization was high for patient data (64.9%), medication administration (47.2%), and prescription and dispensing (21.9%). No respondents used clinical decision support systems. High ePIS usage was associated with receiving supportive supervision (AOR=1.91 [1.18-3.15]), using ePIS for over a year (AOR=2.35 [1.39-4.00]), working in a private hospital (AOR=1.77 [1.06-2.97]), being male (AOR=1.65 [1.02-2.66]), being a nurse (AOR=2.04 [1.16-3.59]), and working in a hospital with an ICT staff size of nine or more (AOR=2.22 [1.33-3.69]) Conclusion Most adopted ePIS functionalities were not aimed at clinical decision-making, and their utilization is notably low. Adherence to established guidelines and regular monitoring of system and user performance are needed.